COMBINED MEDICATIONS IN THE TREATMENT OF THE COUGH IN CHILDREN - A.A. Alekseeva; R.M. Torshkhoeva; E.A. Vishneva; Yu.G. Levina; K.S. Volkov (Union of pediatricians of Russia, 2011)
Practically in all the cases of broncho-pulmonary system diseases, including acute bronchitis, the cough occurs as a clinical syndrome. The main cough function - is the restoration of the airway by removing secretions and restore mucociliary transport of bronchial secretions (mucociliary clearance). Among the variety of antitussives the combined drugs are widely used to treat cough. The combination of several active substances in one medicinal product can produce more effective therapy thanks to the multi-directional action of the components, as well as to improve its safety because of the possibility of using lower doses of drugs due to the combined synergies of their impact. The paper presents the experience of using combined medications in the treatment of cough in children. Key words: cough, respiratory diseases, treatment, and antitussive combined medications, children. (Pediatric Pharmacology. - 2011; 8 (5): 98-100.)